Pengaruh Event Sponsorship, Personal Selling, dan Iklan terhadap Brand Image Honda pada Mahasiswa Fakultas Ekonomi dan Bisnis UMS - Maulana, Huda Kurnia, Soepatini, S.E., M.Si., Ph.D (2015)
The purpose of this study is to analyze the influence of event sponsorship, personal selling, and advertising on brand image of Honda perceived by students of Muhammadiyah Surakarta Economic and Business Faculty. This study also tries to reveal the meaningfulness of the model in explaining brand image. This study hopefully will be able to deepen understanding regarding to brand image and can be used as reference for future studies. The hypothesis of this study is it is believed that there is an influence from event sponsorship, personal selling, and advertising on brand image. It is also believed that event sponsorship, personal selling, and advertising are able to explain brand image meaningfully. The population of this study is the entire active students of Muhamadiyah Surakarta Faculty of Economic and Business. Sampling method used is purposive sampling taking 40 respondents into account. This study employs multiple regression test. The first conclussion found by this study is event sponsorship does not influence brand image, neither does personal selling. On contrary, it is concluded that there is influence of advertising on brand image. It is also found that event sponsorship, personal selling, and advertising is a model that can explain brand image meaningfully. Finally, this study sugessts Honda to maximize its advertising campaign and to invest more cautiosly on event sponsorship and personal selling. Brand image, brand equity, event sponsorship, personal selling, advertising